Jordan : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The Selected Issues paper on Jordan analyzes the Jordanian dinar, which has historically operated within a fixed exchange rate regime. The deterioration in 2004 and 2005 reflected an exceptionally rapid increase in imports, as the saving-investment balance shifted. Following an improvement in 2006, the current account again deteriorated in 2007 from a negative impact of international food and fuel prices. Import developments have been the single most important determinant of swings in the current account, followed to a lesser extent by the impact of exports and grants.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet